In Silico Identification of Potentially Effective Herbal Inhibitors of SARS-Cov-2 Main Protease by Virtual Screening Method: Potential Anti-COVID-19 Molecules - Dowlati Beirami, Amirreza; Hatamabadi, Dara; Iranpanah, Sayna; Rezaei, Mitrasadat; Ziai, Seyed Ali (Student Research in Translational Medicine, 2020)
Background: The COVID-19 pandemic is a global health emergency caused by SARS-CoV-2. Unfortunately, no effective drugs have been found to date. There is also a major need for new therapies to treat this disease. The main protease is an attractive drug target among coronaviruses due to its important role in the processing of viral RNA-translated polyproteins. Objective of This study was conducted to screen databases of herbal compounds for potential main protease inhibitors. Material and Methods: Natural products from 3 database banks were first tested and filtered by ADME / toxicity, then their molecular energy was minimized, and finally, they were docked into the SARS-CoV-2 main protease and compared with indinavir. Results: The binding energies of 6570 molecules from different herbal compounds comprising databases were tested and five of the molecules with the highest binding energies for SARS-CoV-2 main protease docking were selected and key interactions were studied. Conclusion: In conclusion, five herbal compounds including Sodwanone B, Cyclomulberrin, and a glycosylated derivative of kaempferol had lower docking energy compared to indinavir and were suggested for further research.